PENGARUH JUMLAH UANG BEREDAR DAN SUKU BUNGA TERHADAP INFLASI DI INDONESIA TAHUN 2017 - 2019 - Yasmine, Nur Indriana (Politeknik Negeri Semarang, 2023)
One of the economic indicators used to see or measure the stability of a country's economy is inflation. Inflation is one of the important economic indicators, the rate of change is always sought to be low and stable. Inflation can be measured in various ways, one of which is the IHK (Indeks Harga Konsumen). The level of inflation in a country can be influenced by several factors such as the money supply, interest rates, exchange rates, exports, imports, gross domestic product, and government spending. Bank Indonesia as the monetary authority has an important role in controlling inflation, one of which is monetary policy. This monetary policy is related to the money supply and interest rates which can control existing inflation. In everyday life these two indicators can be monitored directly by the community..